OBSERVATION OF THE BENEFITS OF EAR MASSAGE THERAPY SKILLS IN EAST JAVA - Purnami, Nyilo; Suhariningsih, Suhariningsih; Adianti, Myrna; Septriana, Maya; Frederika, Edith; Puspita, Dwi Indah (Journal of Community Medicine and Public Health Research, 2020)
The high number of patients who come for ear therapy with massage skills, the P3T Center intends to carry out an observational screening of ear therapy. This screening aims to find out how the diagnostic method and application of ear therapy with massage skills and the benefits of ear therapy to overcome the problem of hearing loss (hearing impairment). This screening design uses an observational method in which the researcher makes observations and interviews with respondents. Data collection techniques were carried out by looking at the results of the examination of respondents' hearing tests and the results of interviews with respondents. Patient therapy results in 18 people (60%) no progress or the same as the original condition. this shows that therapy can be said to be ineffective in curing ear disorders. The results of the audiometry examination of the right and left ear stated that none of the patients was normal. Even though there are patients who claim to be able to hear loud sounds in the questionnaire, it is not supported by audiometry results. So it can be concluded that ear therapy with massage skills has no impact on patients suffering from hearing loss.